A high-entropy perovskite air electrode material with abundant alkali metals at the A site and its application in proton ceramic fuel cells
By using A-position alkali metal-rich high-entropy perovskite oxide air electrode material in proton ceramic fuel cells, the problems of insufficient reaction force and serious polarization loss at medium and low temperatures are solved, high oxygen reduction activity and excellent conductivity are achieved, and the performance of the fuel cell is improved.
Patent Information
- Application Number
- CN202411081989.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-08-08
AI Technical Summary
The existing proton ceramic fuel cell (PCFC) air electrode materials show insufficient reaction power and severe polarization losses at medium and low temperatures, resulting in a degradation of battery performance and limiting its commercial application.
High entropy perovskite oxides with abundant alkali metal at A position are used as air electrode materials, and the chemical formula is ABO3-δ, where A is one or more of Li, Na, K, Rb, Cs, Ba, Sr, Pr and La, and B is Fe, and is prepared by sol-gel method or high-temperature solid phase method.
The material exhibits high oxygen reduction activity at medium and low temperatures, has excellent conductivity and low oxygen reduction polarization impedance, and significantly improves the performance of proton ceramic fuel cells.
Smart Images

Figure CN118983452B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a high-entropy perovskite air electrode material with an excess of alkali metals at the A position and an application thereof in a proton ceramic fuel cell. Background Art
[0002] Protonic ceramic fuel cells (PCFCs) have been widely studied because of their advantages such as low proton conduction activation energy, high ion conductivity, and no water dilution effect on the fuel gas side. However, due to the high operating temperature of PCFC (>800°C), a series of device problems have been brought about, which not only seriously affects the operating life of the battery, but also brings expensive operating costs, thus limiting its commercial application. For this reason, in order to promote its commercialization, people have been committed to reducing the operating temperature of PCFC as much as possible in recent years. However, as the operating temperature decreases, the reaction kinetics of the air electrode (also known as the cathode) will become extremely slow, resulting in severe polarization losses, causing the overall performance of the battery to drop sharply. Therefore, studying air electrodes with high oxygen reduction performance at medium and low temperatures is the key to promoting the commercialization of PCFC.
[0003] As research continues to deepen, people have found that high-entropy perovskite oxides have superior performance as PCFC air electrodes, but due to the diversity of elements, any slight change will increase the complexity of the crystal structure. Alkali metals can promote the sintering of materials due to their low melting points, which is beneficial to phase formation. At the same time, alkali metals help to improve their electronic and ionic conductivity in the air atmosphere and increase the content of oxygen vacancies in the material; and there are very few cases reported on the application of the modification method of improving the electrochemical performance of proton ceramic fuel cell cathode materials by alkali metal abundance. In summary, designing a high-entropy perovskite oxide with alkali metal abundance at the A site as an air electrode material is of great significance to promote the commercialization of PCFC. Summary of the invention
[0004] In order to solve the problem that the existing air electrode materials are difficult to use in medium and low temperature (400-800℃) PCFC, the present invention proposes a high-entropy perovskite air electrode material with excess alkali metal at the A site and its application in proton ceramic fuel cells, so that the electrode material has high oxygen reduction activity at medium and low temperatures.
[0005] To achieve the above objectives, the present invention provides a high entropy perovskite air electrode material with an excess of alkali metals at the A position, the general chemical formula of which is ABO 3-δ , wherein A is one or more of Li, Na, K, Rb, Cs, Ba, Sr, Pr and La, B is Fe, δ is the oxygen vacancy concentration, and 0<δ<1.
[0006] Furthermore, the molecular formula of the high entropy perovskite air electrode material with an excess of alkali metals at the A position is MxBa 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ , where M is one of Li, Na, K, Rb, and Cs, and 0.2<x≤0.4, δ is the oxygen vacancy concentration, and 0<δ<1. The subscript numbers of each element represent the stoichiometric number of the corresponding element.
[0007] Furthermore, the chemical formula is K 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ .
[0008] The present invention also provides a method for preparing the high-entropy perovskite air electrode material with abundant alkali metal at the A position, which is prepared by a sol-gel method or a high-temperature solid-phase method.
[0009] Furthermore, the sol-gel method comprises the following steps:
[0010] The raw materials of each element are weighed according to the stoichiometric ratio, dissolved in water to obtain solution A, ethylenediaminetetraacetic acid, citric acid and ammonia water are dissolved in water to obtain solution B, and then the solution B is transferred to the solution A to obtain a mixed solution, the pH is adjusted to weak acidity, heated, stirred and dried to obtain a solid precursor, and the solid precursor is calcined to obtain the high-entropy perovskite air electrode material with an excess of alkali metal at the A position.
[0011] Furthermore, the molar ratio of metal ions, ethylenediaminetetraacetic acid, citric acid and ammonia water in the mixed solution is 1:1:2:10, the calcination temperature is 900-1000°C, the time is 5-10h, and the pH is adjusted to weak acidity by using ammonia water to adjust the pH to 6-7.
[0012] Furthermore, the sol-gel method specifically comprises the following steps:
[0013] The metal element raw materials are dissolved in ultrapure water in sequence according to the stoichiometric ratio to form a solution A; ethylenediaminetetraacetic acid (EDTA), citric acid (CA) and ammonia water are dissolved in ultrapure water to form a solution B; then the solution B is poured into the solution A to obtain a mixed solution, wherein the molar ratio of metal ions, ethylenediaminetetraacetic acid, citric acid and ammonia water in the mixed solution is 1:1:2:10, and the pH value of the solution is adjusted to 6-7 by adding ammonia water, and the solution is placed on a heating table for heating and stirring until a dark red viscous gel is formed; the obtained gel is placed in a forced air drying oven, and dried at 200-250°C for 5-10h to obtain a black sponge-like solid precursor, and the obtained black precursor is placed in a muffle furnace and calcined at 900-1000°C for 5-10h to obtain the high entropy perovskite air electrode material with excess alkali metal at the A position.
[0014] Furthermore, the high temperature solid phase method comprises the following steps:
[0015] The raw materials of each element are weighed according to the stoichiometric ratio, anhydrous ethanol is added and ball-milled to obtain a dispersed slurry, and a solid precursor is obtained after drying. The solid precursor is calcined to obtain the high-entropy perovskite air electrode material with an excess of alkali metal at the A position.
[0016] Furthermore, the ball milling time is 5-10 hours, the rotation speed is 400r / min, and the calcination temperature is 1000-1200°C, and the time is 10-15 hours.
[0017] Furthermore, the high temperature solid phase method specifically comprises the following steps:
[0018] The metal element raw materials are placed in a high-energy ball mill in sequence according to the stoichiometric ratio, and anhydrous ethanol is used as the liquid medium. The mixed slurry with uniformly dispersed powder is obtained at a high speed for 5-10 hours. The obtained slurry is transferred to a surface dish and placed in a forced air drying oven. It is dried at 60-80°C for 3-5 hours to obtain a solid precursor. The precursor is then placed in a muffle furnace and calcined at 1000-1200°C for 10-15 hours to obtain the high-entropy perovskite air electrode material with excess alkali metal at the A position.
[0019] The present invention also provides the use of the A-site alkali metal-rich high-entropy perovskite air electrode material in a proton ceramic fuel cell.
[0020] Compared with the prior art, the present invention has the following advantages and technical effects:
[0021] (1) The high entropy perovskite air electrode material of the present invention exhibits excellent oxygen reduction electrocatalytic performance in proton ceramic fuel cells by a novel method of enriching the alkali metal element at the A position.
[0022] (2) The high entropy perovskite air electrode material prepared by the present invention has a cubic perovskite structure, has excellent electrical conductivity, and has a low oxygen reduction polarization impedance, so that the electrode material has high oxygen reduction activity at medium and low temperatures, and is an excellent high-performance PCFC air electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0024] Figure 1 is K in Example 1 0.4 BSPLF and K in Comparative Example 1 0.2 X-ray diffraction spectrum of BSPLF;
[0025] Figure 2 is K in Example 1 0.4 BSPLF and K in Comparative Example 1 0.2 Infrared spectrum of BSPLF;
[0026] Figure 3 is K in Example 1 0.4 BSPLF and K in Comparative Example 1 0.2 Conductivity characterization results of BSPLF;
[0027] Figure 4 is K in Example 1 0.4 Polarization impedance spectrum of the symmetrical battery prepared by BSPLF;
[0028] Figure 5 K in Comparative Example 1 0.2 Polarization impedance spectrum of the symmetrical battery prepared by BSPLF. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] The embodiment of the present invention provides a high entropy perovskite air electrode material with abundant alkali metal at the A position, and the chemical formula is ABO 3-δ , wherein A is one or more of Li, Na, K, Rb, Cs, Ba, Sr, Pr and La, B is Fe, δ is the oxygen vacancy concentration, and 0<δ<1.
[0035] In a preferred embodiment of the present invention, the molecular formula of the high entropy perovskite air electrode material with abundant alkali metal at the A position is MxBa 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ , where M is one of Li, Na, K, Rb, and Cs, and 0.2<x≤0.4, δ is the oxygen vacancy concentration, and 0<δ<1. The subscript numbers of each element represent the stoichiometric number of the corresponding element.
[0036] More preferably, its chemical formula is K 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ .
[0037] The embodiment of the present invention also provides a method for preparing the high-entropy perovskite air electrode material with abundant alkali metal at the A position, which is prepared by a sol-gel method or a high-temperature solid-phase method.
[0038] In a preferred embodiment of the present invention, the sol-gel method comprises the following steps:
[0039] The raw materials of each element are weighed according to the stoichiometric ratio, dissolved in water to obtain solution A, ethylenediaminetetraacetic acid, citric acid and ammonia water are dissolved in water to obtain solution B, and then the solution B is transferred to the solution A to obtain a mixed solution, the pH is adjusted to weak acidity, heated, stirred and dried to obtain a solid precursor, and the solid precursor is calcined to obtain the high-entropy perovskite air electrode material with excess alkali metal at the A position; more preferably, the molar ratio of metal ions, ethylenediaminetetraacetic acid, citric acid and ammonia water in the mixed solution is 1:1:2:10, the calcination temperature is 900-1000°C, the time is 5-10h, and the pH is adjusted to weak acidity by adjusting the pH to 6-7 with ammonia water.
[0040] More specifically, the sol-gel method comprises the following steps:
[0041] According to the stoichiometric ratio, the metal element raw materials are dissolved in ultrapure water in sequence to form a solution A, ethylenediaminetetraacetic acid (EDTA), citric acid (CA) and ammonia water are dissolved in ultrapure water to form a solution B, and then the solution B is poured into the solution A to obtain a mixed solution, wherein the molar ratio of metal ions, ethylenediaminetetraacetic acid, citric acid and ammonia water in the mixed solution is 1:1:2:10, and the pH value of the solution is adjusted to 6-7 by adding ammonia water, and the solution is placed on a heating table for heating and stirring until a dark red viscous gel is formed, and the obtained gel is placed in a blast drying oven, and dried at 200-250°C for 5-10h to obtain a black sponge-like solid precursor, and the obtained black precursor is placed in a muffle furnace, and roasted at 900-1000°C for 5-10h to obtain the high entropy perovskite air electrode material with excess alkali metal at the A position.
[0042] In a preferred embodiment of the present invention, the high temperature solid phase method comprises the following steps:
[0043] The raw materials of each element are weighed according to the stoichiometric ratio, anhydrous ethanol is added and ball-milled to obtain a dispersed slurry, a solid precursor is obtained after drying, and the solid precursor is calcined to obtain the high-entropy perovskite air electrode material with excess alkali metal at the A position; more preferably, the ball milling time is 5-10h, the rotation speed is 400r / min, the calcination temperature is 1000-1200°C, and the time is 10-15h.
[0044] More specifically, the high temperature solid phase method comprises the following steps:
[0045] The metal element raw materials are placed in a high-energy ball mill in sequence according to the stoichiometric ratio, and anhydrous ethanol is used as the liquid medium. The mixed slurry with uniformly dispersed powder is obtained at a high speed for 5-10 hours. The obtained slurry is transferred to a surface dish and placed in a forced air drying oven. It is dried at 60-80°C for 3-5 hours to obtain a solid precursor. The precursor is then placed in a muffle furnace and calcined at 1000-1200°C for 10-15 hours to obtain the high-entropy perovskite air electrode material with excess alkali metal at the A position.
[0046] The embodiment of the present invention also provides the use of the high entropy perovskite air electrode material with abundant alkali metal at the A site in a proton ceramic fuel cell.
[0047] All raw materials used in the examples of the present invention are commercially available.
[0048] The technical solution of the present invention is further illustrated by the following embodiments.
[0049] Example 1
[0050] Preparation of a high-entropy perovskite air electrode material K with alkali-rich A-site by sol-gel method 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ , specifically including the following steps:
[0051] (1) Weigh 0.8651 g of K3C6H5O7·H2O, 1.0454 g of Ba(NO3)2, 0.8465 g of Sr(NO3)2, 1.7404 g of Pr(NO3)3·6H2O, 1.7320 g of La(NO3)3·6H2O and 8.08 g of Fe(NO3)3·9H2O, and add them to 200 mL of ultrapure water to dissolve them to form solution A;
[0052] (2) According to the molar ratio of total metal ions, ethylenediaminetetraacetic acid (EDTA), citric acid (CA) and ammonia water in solution A being 1:1:2:10, 11.69 g of EDTA, 15.37 g of CA and 30.8 mL of ammonia water were weighed and dissolved in 100 mL of ultrapure water to form solution B;
[0053] (3) After adding solution B to solution A, an appropriate amount of ammonia water is added dropwise to make the pH value of the solution reach between 6 and 7, and then the solution is placed in a magnetic stirrer and heated and stirred until the water is completely evaporated and a gel is formed;
[0054] (4) placing the obtained gel-like substance in a forced air drying oven and drying it at 250° C. for 5 h to obtain a black sponge-like precursor;
[0055] (5) The obtained precursor was placed in a muffle furnace and calcined at 900°C for 5 h to obtain the desired high entropy perovskite air electrode material K 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ (K 0.4 BSPLF).
[0056] Example 2
[0057] A high-entropy perovskite air electrode material K with abundant alkali metals at the A site was prepared by high-temperature solid-phase method 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ , specifically including the following steps:
[0058] (1) Weigh 0.5528 g of K2CO3, 0.7893 g of BaCO3, 0.5905 g of SrCO3, and 0.6810 g of Pr6O 11 , 0.6516 g of La2O3 and 3.1938 g of Fe2O3 in a ball mill;
[0059] (2) using anhydrous ethanol as the liquid medium and ball milling at a speed of 400 rpm for 10 h to obtain a slurry with uniform powder dispersion;
[0060] (3) The obtained slurry was transferred to a watch glass, placed in a forced air drying oven, and dried at 80° C. for 5 h to obtain a solid precursor;
[0061] (4) The obtained precursor was placed in a muffle furnace and calcined at 1100°C for 10 h to obtain the desired high entropy perovskite air electrode material K 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ (K 0.4 BSPLF).
[0062] Comparative Example 1
[0063] Preparation of a high entropy perovskite air electrode material K by sol-gel method 0.2 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ , specifically including the following steps:
[0064] (1) Weigh 0.4326 g of K3C6H5O7·H2O, 1.0454 g of Ba(NO3)2, 0.8465 g of Sr(NO3)2, 1.7404 g of Pr(NO3)3·6H2O, 1.7320 g of La(NO3)3·6H2O and 8.08 g of Fe(NO3)3·9H2O, and add them to 200 mL of ultrapure water for dissolution to form solution A;
[0065] (2) According to the molar ratio of total metal ions, ethylenediaminetetraacetic acid (EDTA), citric acid (CA) and ammonia water in solution A being 1:1:2:10, 11.69 g of EDTA, 15.37 g of CA and 30.8 mL of ammonia water were weighed and dissolved in 100 mL of ultrapure water to form solution B;
[0066] (3) After adding solution B to solution A, an appropriate amount of ammonia water is added dropwise to make the pH value of the solution reach between 6 and 7, and then the solution is placed in a magnetic stirrer and heated and stirred until the water is completely evaporated and a gel is formed;
[0067] (4) placing the obtained gel-like substance in a forced air drying oven and drying it at 250° C. for 5 h to obtain a black sponge-like precursor;
[0068] (5) The obtained precursor was placed in a muffle furnace and calcined at 900°C for 5 h to obtain the desired high entropy perovskite air electrode material K 0.2 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ (K 0.2 BSPLF).
[0069] Comparative Example 2
[0070] Preparation of a high entropy perovskite air electrode material K by high temperature solid phase method 0.2 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ , specifically including the following steps:
[0071] (1) Weigh 0.2764 g of K2CO3, 0.7893 g of BaCO3, 0.0.5905 g of SrCO3, and 0.6810 g of Pr6O 11 , 0.6516 g of La2O3 and 3.1938 g of Fe2O3 in a ball mill;
[0072] (2) using anhydrous ethanol as the liquid medium and ball milling at a speed of 400 rpm for 10 h to obtain a slurry with uniform powder dispersion;
[0073] (3) The obtained slurry was transferred to a watch glass, placed in a forced air drying oven, and dried at 80° C. for 5 h to obtain a solid precursor;
[0074] (4) The obtained precursor was placed in a muffle furnace and calcined at 1100°C for 10 h to obtain the desired high entropy perovskite air electrode material K 0.2 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ (K 0.2 BSPLF).
[0075] Performance Testing
[0076] 1. X-ray diffraction spectrum characterization
[0077] The high entropy perovskite air electrode material K obtained in Example 1 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ (K 0.4 BSPLF) and the high entropy perovskite air electrode material K obtained in Comparative Example 1 0.2 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ (K 0.2 The X-ray diffraction spectrum of BSPLF) is shown in Figure 1 It can be seen that the peak intensity of the high-entropy material with excess alkali metals is higher and the crystallinity is better; the main peak shifts to the right and the interplanar spacing decreases.
[0078] 2. Infrared spectroscopy characterization
[0079] The high entropy perovskite air electrode material K obtained in Example 1 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ (K 0.4 BSPLF) and the high entropy perovskite air electrode material K obtained in Comparative Example 1 0.2 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO3-δ (K 0.2 The infrared spectrum of BSPLF) is shown in Figure 2 , it can be seen from the figure that the peak vibration positions of all electrode materials are basically the same, but the metal fingerprint region (1300-400cm -1 )'s tensile vibration peak intensity is significantly enhanced after alkali metal abundance.
[0080] 3. Conductivity Characterization
[0081] The high entropy perovskite air electrode material K obtained in Example 1 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ (K 0.4 The BSPLF) was ground again, and the ground powder was added with an appropriate amount of 10% PVA solution, mixed evenly, and then dry pressed in a steel casting mold. The prepared rectangular bars were sintered at 1100°C in air atmosphere for 5 hours to obtain a dense sample.
[0082] The conductivity of the sample was tested by using the direct current four-probe method and a Keithley 2420 digital source meter. Conductive silver glue was used to connect the conductive silver wire to both ends of the sample and about 2 mm away from both ends. During the test, a constant current was applied to both ends of the strip sample, and a potential difference was taken between the two ends in the middle. The test temperature range was 500-800℃, and the data collection interval was 10℃ per point.
[0083] The conductivity characterization results of the rectangular samples prepared using the high entropy perovskite air electrode materials obtained in Example 1 and Comparative Example 1 are shown in Figure 3 It can be seen that the conductivity test in the temperature range of 500-800℃ shows that the alkali metal-rich high entropy perovskite oxide material K at 600℃ 0.4 The conductivity of BSPLF is compared with K 0.2 The BSPLF material has increased by ~9 times. Since alkali metals have the advantage of improving electrical conductivity, the performance of high entropy materials in proton ceramic fuel cells has been improved by using alkali metal abundance.
[0084] 4. Polarization impedance characterization
[0085] The high entropy perovskite air electrode material K obtained in Example 1 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ (K 0.4BSPLF) was mixed with isopropanol, ethylene glycol and glycerol in a mass ratio of 4:2.4:8:40 and subjected to high-energy ball milling to prepare air electrode spray slurry. The dry-pressed dense electrolyte sheet was placed on a heating table at 180°C, and the air electrode spray slurry was evenly sprayed on both sides of the electrolyte using a spray gun. It was then placed in a muffle furnace and calcined at 900°C for 2h to obtain a K 0.4 BSPLF|BZCYYb|K 0.4 Symmetrical battery of BSPLF.
[0086] The prepared symmetrical battery was assembled into a mold and placed in a tubular muffle furnace, and polarization impedance testing was performed using a Solartron 1260+1287 electrochemical workstation in a temperature range of 500-700°C and humidified air, with a gas flow rate of 80 mL / min.
[0087] The A-site alkali metal-rich high entropy material K prepared in Example 1 is used. 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ The symmetrical battery and the stoichiometric material K prepared in Comparative Example 1 0.2 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ Polarization impedance tests were performed on symmetrical batteries and compared. Figure 4 and Figure 5 are respectively K of Example 1 0.4 K of BSPLF and Comparative Example 1 0.2 Polarization impedance spectrum of BSPLF tested in humid air at a temperature range of 500-700℃. 0.4 The polarization impedance of BSPLF reaches 0.20Ωcm at 600℃ 2 , and K 0.2 BSPLF 0.42Ωcm 2 This represents a 52% decrease.
[0088] The preparation methods of the symmetrical batteries in other embodiments and comparative examples are the same as above.
[0089] The measurement results of Example 2 and Comparative Example 2 are the same as those of Example 1 and Comparative Example 1.
[0090] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. Application of high entropy perovskite air electrode materials with excess alkali metals at the A position in proton ceramic fuel cells, characterized in that: The molecular formula of the high entropy perovskite air electrode material with abundant alkali metal at the A position is MxBa 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ , where M is one of Li, Na, K, Rb, and Cs, and 0.2<x≤0.4, δ is the oxygen vacancy concentration, and 0<δ<1; The high entropy perovskite air electrode material with abundant alkali metal at the A position is prepared by a sol-gel method or a high-temperature solid phase method; The sol-gel method comprises the following steps: Weigh the raw materials of each element according to the stoichiometric ratio, dissolve them in water to obtain solution A; dissolve ethylenediaminetetraacetic acid, citric acid and ammonia water in water to obtain solution B; then transfer the solution B to the solution A to obtain a mixed solution, and adjust the pH to weak acidity; heat, stir and dry to obtain a solid precursor, and calcine the solid precursor to obtain the high entropy perovskite air electrode material with excess alkali metal at the A position; The high temperature solid phase method comprises the following steps: The raw materials of each element are weighed according to the stoichiometric ratio, anhydrous ethanol is added and ball-milled to obtain a dispersed slurry, and a solid precursor is obtained after drying. The solid precursor is calcined to obtain the high-entropy perovskite air electrode material with an excess of alkali metal at the A position.
2. The use of the high entropy perovskite air electrode material with excess alkali metal at the A position according to claim 1 in a proton ceramic fuel cell, characterized in that: The chemical formula is K 0.4 Ba 0.2 Sr 0.2 Pr 0.2 La 0.2 FeO 3-δ .
3. The use of the high entropy perovskite air electrode material with excess alkali metal at the A position according to claim 1 in a proton ceramic fuel cell, characterized in that: In the sol-gel method, the molar ratio of metal ions, ethylenediaminetetraacetic acid, citric acid and ammonia water in the mixed solution is 1:1:2:10; the calcination temperature is 900-1000°C and the time is 5-10h; and the pH is adjusted to weak acidity by using ammonia water to adjust the pH to 6-7.
4. The use of the high entropy perovskite air electrode material with excess alkali metal at the A position according to claim 1 in a proton ceramic fuel cell, characterized in that: In the high temperature solid phase method, the calcination temperature is 1000-1200° C. and the calcination time is 10-15 hours.
Citation Information
Patent Citations
Perovskite material with excessive A site, preparation method and application of perovskite material in catalytic treatment of organic wastewater
CN113231068A
High-entropy perovskite membrane and application in oxygen separation and membrane reactor
CN113967413A